Gains from highyielding varieties with and without complementary technologies: the case of improved cowpea in northern Nigeria - Alene, Arega D.; Manyong, Victor M. (2007)
This paper examines the adoption and impact of selective and whole package adoption of improved cowpea involving new variety, insect control, fertilizer, and best bet cropping pattern in northern Nigeria. A farm income model that explicitly accounts for endogenous technology adoption was used to assess the impacts. Results show that adoption of the whole package, rather than adoption of selected components, had a significant impact on productivity and incomes, which was in turn due largely to the recommended cropping pattern. Education, credit, extension contact, access to improved seeds, and participation in on-farm technology evaluations are significantly related to the intensification of improved cowpea production. The paper concludes with implications for policy to enhance productivity and household incomes.